Weierstrass formula for minimal surfaces in Heisenberg group - Figueroa Serrudo, Christian Bernardo (Pro Mathematica, 1999)
In this paper we study the Gauss map of minimal surfaces in the Heisenberg group, H?. We obtain a representation formula for minimal surfaces in H? by means of the Gauss map. As consequence we conclude that: The Gauss map of a minimal surface of H? is antiholomorphic if the minimal surface is a plane.